A case of emphysematous cystitis - Amano, Toshiyasu (Hinyokika kiyo. Acta urologica Japonica, 2005)
A 60-year-old woman visited our clinic with a complaint of gross hematuria. She was under treatment for rheumatoid arthritis, amyloidosis and diabetes mellitus at the Departments of Orthopedic Surgery and Internal Medicine. The results of a urine analysis showed protein urine, glucose urine, hematopyuria and bacteriuria. The diagnosis of emphysematous cystitis was made from radiography, ultrasonogram and cystoscopic findings. Antibiotics were administered effectively. However, one month later, bilateral hydronephrosis was identified by a computed tomographic scan performed by the Department of Internal Medicine. The bilateral hydronephrosis was brought on by urinary retention caused by a neurogenic bladder disorder. Thus, an indwelling catheter followed by intermittent catheterization was performed and cholinergic medication prescribed successfully